Emerging roles of long non-coding RNAs in osteosarcoma - Liao, Xun; Wei, Rong; Zhou, Junxiu; Wu, Ke; Li, Jiao (Frontiers in Molecular Biosciences, 2024)
Osteosarcoma (OS) is a highly aggressive and lethal malignant bone tumor that primarily afflicts children, adolescents, and young adults. However, the molecular mechanisms underlying OS pathogenesis remain obscure. Mounting evidence implicates dysregulated long non-coding RNAs (lncRNAs) in tumorigenesis and progression. These lncRNAs play a pivotal role in modulating gene expression at diverse epigenetic, transcriptional, and post-transcriptional levels. Uncovering the roles of aberrant lncRNAs would provide new insights into OS pathogenesis and novel tools for its early diagnosis and treatment. In this review, we summarize the significance of lncRNAs in controlling signaling pathways implicated in OS development, including the Wnt/β-catenin, PI3K/AKT/mTOR, NF-κB, Notch, Hippo, and HIF-1α. Moreover, we discussed the multifaceted contributions of lncRNAs to drug resistance in OS, as well as their potential to serve as biomarkers and therapeutic targets. This review aims to encourage further research into lncRNA field and the development of more effective therapeutic strategies for patients with OS.